Theoretical Vulnerability Analysis of Individual Components of Class I – Micro Drone Against Small Arms Fire - Ivan PEMČÁK (Teoretyczna analiza podatności poszczególnych komponentów mikrodronów klasy I na ostrzał z broni strzeleckiej, 2024)
This article is a continuation of a series of publications dealing with defence against Class I UAVs. Previous publications concerned the capabilities and range of detecting drones [1, 2], as well as experimental research on the effectiveness of using shotguns to defend against UAVs and the impact of such weapons on selected drone elements [3-5]. This paper examines the hit probability of individual drone components depending on the drone’s orientation in space. This work aims to theoretically determine the probability of disabling a drone with a single hit from an assault rifle. Due to its widespread use, the DJI Mavic 2 drone was chosen as an example for study. The theoretical knowledge and assumptions are elaborated in this thesis. One of the novelties in relation to previous works is the presentation in this article of the possibility of increasing the survivability of drones on the battlefield. Practical verification of the modelled data is the subject of further study and experiments.
Keywords: Eksploatacja mikrodronów